Pelayanan Bimbingan Dan Konseling Tingkat Sekolah Dasar Se-Kota Surakarta - Maulana, Muhammad Arief; Maynawati, Aldila Fitri Radite Nur (JURNAL KONSELING GUSJIGANG, 2018)
The goal of research to figure out the implementation of guidance and counseling programs at the primary level. Research done in the elementary school in the city of Surakarta has accredited A (very good). Research methods using qualitative research with the aim of providing factual conditions that occur in the field related to the execution of counseling program in elementary school. Data retrieval using interview techniques and observations conducted by the proposers. Observation and interview instruments validated by experts in the field of guidance counseling in order to obtain valid data and reliability. Testing the validity of the data by using the technique of triangulation of sources. The research results obtained that the guidance counseling service program in elementary school city of Surakarta has not done well. There are still many elementary schools that don't yet have the power guidance counseling teacher, and obstacles that encounter i.e. guidance counseling teacher in primary school is still a difficulty in finding the needs of students through the instrumentation and application evaluation and activities follow-up.